Influence of everyday bolus consistencies in different body positions on high‐resolution esophageal pressure topography (HREPT) parameters. Issue 3 (7th February 2014) - Hasan, Y.; Go, J.; Hashmi, S. M.; Valestin, J.; Schey, R.
Summary The standard protocol for esophageal manometry involves placing the patient in the supine position with head turned to left (supine head left [SHL]) while evaluating liquid bolus swallows. Routinely, semisolid or solid boluses are not evaluated. Currently, the daily American diet includes up to 40% solid or semisolid texture. Thus far, the data on the effect of different bolus on high‐resolution esophageal pressure topography (HREPT) parameters are scarce. This study aims to evaluate the effect of every day bolus consistencies in different body positions on HREPT variables. HREPT was performed on healthy volunteers with a modified protocol including liquid swallows in the SHL position followed by applesauce (semisolid), cracker (solid), and marshmallow (soft solid) in three different positions (SHL, sitting, and standing). A total of 38 healthy adult subjects (22 males and 16 females, median age = 27, and mean body mass index = 25) were evaluated. The resting upper esophageal sphincter pressure was significantly different while subjects swallowed crackers, applesauce, and marshmallows in most positions compared with liquid SHL (P < 0.05). The lower esophageal sphincter, contractile front velocity, and distal contractile integral pressures did not differ in all different consistencies compared with SHL. The integrated relaxation period was significantly higher with solid bolus compared with liquid bolus only in SHL position. The intrabolus pressure was significantly different with solid and soft solid boluses in all postures compared to liquid SHL. The American diet consistency affects upper esophageal sphincter pressure and partially integrated relaxation period and intrabolus pressure in various positions. Semisolid bolus swallows do not cause substantial pressure changes and are safe for evaluation and maintaining adequate caloric intake in patients with dysphagia who cannot tolerate solids.